Integrasi Nilai-Nilai Hukum Islam dalam Pembaruan Hukum Pidana Nasional Terkait Tindak Pidana Zina dan Kohabitasi - Roli Pebrianto; Muhammad Panji Prabu Dharma; Noviana Noviana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the regulation of adultery and cohabitation (living together without marriage) from the perspective of Islamic law and Indonesian positive law, especially after the enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP). In Islamic law, adultery is a hudud crime that has strict and permanent sanctions (qat'i). Islamic law considers adultery as an act that damages morality, honor, and lineage, and provides severe punishment for the perpetrators. The purpose of implementing this punishment is to maintain social integrity and protect the family as the smallest unit in society. Cohabitation, which is considered an illegitimate relationship according to Islamic law, is seen as a form of adultery that is not tolerated both socially and legally. Therefore, this act is not only considered a violation of religious norms, but also a threat to the desired social order in Islam. Meanwhile, in the context of Indonesian positive law, the 2023 Criminal Code expands the formulation of the crime of adultery and explicitly regulates cohabitation as a criminal offense. Based on this provision, adultery and cohabitation can be prosecuted, although they are still classified as absolute complaint offenses, meaning that these acts can only be prosecuted if there is a report from an interested party. This shows that although there are differences in law enforcement between Islamic law and positive law, both share a common goal: to protect morality and public order. The approach used in this study is normative juridical with a qualitative analysis method of Islamic legal norms and national statutory provisions. This study aims to compare the perspectives of the two legal systems on adultery and cohabitation, and to find common ground between the two.